HAK LAYANAN KESEHATAN MENTAL DALAM PERPEKTIF HUKUM DAN KONSTITUSI - Luhukay, Roni Sulistyanto (Paulus Law Journal, 2024)
https://docs.google.com/document/d/1q9V-rE21sAUK7U2awWuQwFmB1VXd8t_0/edit?usp=sharing&ouid=117409050110972185272&rtpof=true&sd=true